Microelectrode arrays in combination with in vitro models of spinal cord injury as tools to investigate pathological changes in network activity: facts and promises - Mladinic, Miranda; Nistri, Andrea (Frontiers in Neuroengineering, 2013)
Microelectrode arrays (MEAs) represent an important tool to study the basic characteristics of spinal networks that control locomotion in physiological conditions. Fundamental properties of this neuronal rhythmicity like burst origin, propagation, coordination and resilience can, thus, be investigated at multiple sites within a certain spinal topography and neighbouring circuits. A novel challenge will be to apply this technology to unveil the mechanisms underlying pathological processes evoked by spinal cord injury. To achieve this goal, it is necessary to fully identify spinal networks that make up the locomotor central pattern generator (CPG) and to understand their operational rules. In this review, the use of isolated spinal cord preparations from rodents, or organotypic spinal slice cultures is discussed to study rhythmic activity. In particular, this review surveys our recently developed in vitro models of spinal cord injury by evoking excitotoxic (or even hypoxic/dysmetabolic) damage to spinal networks and assessing their impact on rhythmic activity and cell survival. These pathological processes which evolve via different cell death mechanisms are discussed as a paradigm to apply MEA recording for detailed mapping of the functional damage and its time-dependent evolution.